Early peripheral blood lymphocyte subsets and cytokines in predicting the severity of influenza B virus pneumonia in children - Ma, Lu; Yan, Jingli; Song, Wenliang; Wu, Bo; Wang, Zeyu; Xu, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Children with influenza B virus infection have a higher susceptibility and higher severity of illness. The activation and disorder of immune function play an important role in the severity of influenza virus infection. This study aims to investigate whether early lymphocyte count and cytokines can provide predictive value for the progression in children with influenza B virus pneumonia. Methods: A retrospective cohort study was conducted to analyze the clinical data of children with influenza B virus pneumonia from December 1, 2021, to March 31, 2022, in the National Children's Regional Medical Center (Shengjing Hospital of China Medical University). According to the severity of the disease, the children were divided into a mild group and a severe group, and the clinical characteristics, routine laboratory examination, lymphocyte subsets, and cytokines were compared. Results: A total of 93 children with influenza B virus pneumonia were enrolled, including 70 cases in the mild group and 23 cases in the severe group. Univariate analysis showed that drowsiness, dyspnea, white blood cell (WBC), lymphocytes, monocytes, procalcitonin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase-MB(CK-MB), lactate dehydrogenase (LDH), fibrinogen (FIB), Immunoglobulin M (IgM), lung consolidation, total T cell count, CD4+ T cell count, CD8+ T cell count, NK cell count, NK cell % and B cell % had statistical differences between the mild and severe groups (P<0.05). In multivariate logistic regression analysis, reduced ALT (OR=1.016), FIB (OR = 0.233), CD8+ T cell count (OR = 0.993) and NK cell count (OR = 0.987) were independently associated with the development of severe influenza B virus pneumonia. Conclusions: The levels of T lymphocytes and NK cells were related to the progression of influenza B virus pneumonia in children, and the reduction of CD8+ T cell count and NK cell count can be used as independent risk factors for predicting the severity of influenza B virus pneumonia.